An Analysis of Patient-reported Outcomes in IXORA-S: Comparing Ixekizumab and Ustekinumab over 52 Weeks in Moderate-to-severe Psoriasis - Lluís Puig; Mark Lomaga; Kristin Hollister; Yves Dutronc; Lovisa Berggren; Peter C.M. van de Kerkhof (Medical Journals Sweden, 2020)
Patient-reported outcomes are valuable for assessing new psoriasis therapies. This study investigated patient-reported outcomes in patients with moderate-to-severe plaque psoriasis treated with ixekizumab or ustekinumab, dosed according to their respective labels, for 52 weeks (IXORA-S-NCT02561806). Patient-reported outcomes investigated included patient global assessment, pruritus, skin pain, health-related quality of life, and work productivity. Ixekizumab-treated patients reported greater improvements in patient-reported outcomes sooner after treatment compared with ustekinumab-treated patients, and maintained greater improvements in patient global assessment scores (ixekizumab 0.72, ustekinumab 1.19; p < 0.001), rates of Dermatology Life Quality Index (0, 1) (ixekizumab 71.3%, ustekinumab 56.6%, p < 0.01), and 36-item Short-form Health survey physical component summary score change from baseline (ixekizumab 5.53, ustekinumab 3.28; p < 0.05) at week 52. While clinically meaningful improvements in patient-reported outcomes resulted with either treatment, ixekizumab provided more rapid improvements in patient-reported outcomes and superior outcomes for some assessments through one year of treatment, while maintaining statistically superior improvements in skin severity, as assessed by either physicians or patients.